First Genome Sequence of the Gunnison's Prairie Dog (Cynomys gunnisoni), a Keystone Species and Player in the Transmission of Sylvatic Plague. (11th April 2020) - Tsuchiya, Mirian T N; Dikow, Rebecca B; Cassin-Sackett, Loren
Abstract: Prairie dogs (genus Cynomys ) are a charismatic symbol of the American West. Their large social aggregations and complex vocalizations have been the subject of scientific and popular interest for decades. A large body of literature has documented their role as keystone species of western North America's grasslands: They generate habitat for other vertebrates, increase nutrient availability for plants, and act as a food source for mammalian, squamate, and avian predators. An additional keystone role lies in their extreme susceptibility to sylvatic plague (caused by Yersinia pestis ), which results in periodic population extinctions, thereby generating spatiotemporal heterogeneity in both biotic communities and ecological processes. Here, we report the first Cynomys genome for a Gunnison's prairie dog ( C. gunnisoni gunnisoni ) from Telluride, Colorado (USA). The genome was constructed using a hybrid assembly of PacBio and Illumina reads and assembled with MaSuRCA and PBJelly, which resulted in a scaffold N50 of 824 kb. Total genome size was 2.67 Gb, with 32.46% of the bases occurring in repeat regions. We recovered 94.9% (91% complete) of the single copy orthologs using the mammalian Benchmarking Universal Single-Copy Orthologs database and detected 49, 377 gene models (332, 141 coding regions). Pairwise Sequentially Markovian Coalescent showed support for long-term stable population size followed by a steady decline beginning near the end of the Pleistocene, as well as a recent population reduction. The genome will aid in studies of mammalian evolution, disease resistance, and the genomic basis of life history traits in ground squirrels.